A receção da penicilina em Portugal na literatura médico-farmacêutica e na imprensa diária (anos 40-60 do século xx) - Victoria Bell (Ciências e Culturas, 2019)
The discovery and introduction of penicillin into therapeutics changed the prognostic of infectious diseases, altered the path of medicine and saved innumerous lives. It was a major discovery in the history of medicine and represented the starting point for research that led to the discovery of other antibiotics. Portugal was one of the first European countries, non-participant in the II World War, to obtain penicillin for civilian use. Good diplomatic relations between Portugal, Brazil and the United States of America (USA) were decisive in attaining penicillin for our country. Portuguese pharmacists and physicians immediately perceived the significance of the antibiotic and developed innumerous studies pertaining the clinical applications and quality of the antibiotic.